2018
DOI: 10.1515/sjpain-2018-0104
|View full text |Cite
|
Sign up to set email alerts
|

Body image is more negative in patients with chronic low back pain than in patients with subacute low back pain and healthy controls

Abstract: Abstract Background and aims Body image as an increasing research field has been integrated into pain research within the last years. However, research on cognitive-affective dimensions of body image dependent on different pain groups like acute/subacute and chronic pain patients, and healthy controls is still lacking. Therefore, this study aims to explore three dimensions of body image, namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Although our findings were centered on exercise-induced changes in ‘physical efficacy’, corroborating previous findings in chronic pain patients [ 41 ] we have to acknowledge that the observation of no significant changes in ‘health’ and ‘self-acceptance of one’s body’ is not in accord with the entire previous research literature [ 64 , 65 ]. We may speculate, however, that no changes in the individually perceived health status had to be expected in the context of this study, as all participants were healthy and young.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Although our findings were centered on exercise-induced changes in ‘physical efficacy’, corroborating previous findings in chronic pain patients [ 41 ] we have to acknowledge that the observation of no significant changes in ‘health’ and ‘self-acceptance of one’s body’ is not in accord with the entire previous research literature [ 64 , 65 ]. We may speculate, however, that no changes in the individually perceived health status had to be expected in the context of this study, as all participants were healthy and young.…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, participants with a more positive body image are expected to have higher pain thresholds, an assumption that is also supported by the positive correlation between SKEF and HPT in the present study. Previous work has shown that the SKEF, in comparison to other components of the FKKS, is most closely related to pain states [ 41 ]: Patients with chronic or subacute pain states have a more negative body image of ‘physical efficacy’, as compared to healthy controls [ 41 ]. The current longitudinal data extend these cross-sectional findings in patients, by showing that AE modulates precisely the ‘physical efficacy’ dimension of the BI concept.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past decade, unfavorable facets of body image became of increasing interest, that is, perceptual aspects, such as misperceptions of the painful body part (eg, "I can't find it," "It feels as though it has shrunk" 14 ), and cognitive-affective aspects of body image, the latter referring to negative evaluations of one's own body with respect to self-acceptance (eg, "I have more physical deficits than others" 15 ), health (eg, "I often reach my physical limits" 15 ), and physical efficacy (eg, "I am strong" 15 ). [14][15][16][17] Recently, it has been shown that nonathletic patients with LBP reveal a more negative body image than healthy controls, although the direction of this relationship remains open. 17 However, there are inconsistent results regarding athletes.…”
mentioning
confidence: 99%
“…Chou et al [ 10 ] underlined these recommendations and showed that psychological impairments, e.g., sleep disorders, mood fluctuation, depression, and listlessness, are frequent co-morbidities of chronic pain. A central characteristic of patients with chronic pain is their negative body perception [ 11 ], inhibiting cognitive access to therapy [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%